Labor Pain in Second Stage Active Phase Inpartu Mothers on the Effect of Endorphin Massage in Regional General Hospitals - Asikin, Siti Badria; Qamarya, Nurul; Bahrun, Suriani (International Journal of Health Sciences, 2025)
Labor pain is one of the most intense experiences experienced by women during the birth process. The intensity of pain increases along with the development of the labor stage, especially in the active phase of the second stage. Non-pharmacological interventions such as endorphin massage have been introduced as a safe and effective alternative method to reduce pain. This study aims to determine the effect of endorphin massage on pain intensity in mothers in the active phase of the second stage of labor at the Regional General Hospital. This study used a quasi-experimental design with a pretest-posttest approach. control group. The results showed that endorphin massage can significantly reduce pain intensity. This intervention is recommended to be implemented as part of pain management in the labor process.